Effectiveness test of red shoot leaf extract (Syzygium myrtifolium Walp.) as a natural antiperspirant in inhibiting sweat production and the growth of Pseudomonas aeruginosa bacteria that cause body odor - Arnita, Lisna; Rasyidah, Rasyidah; Mayasari, Ulfayani (Bioma : Berkala Ilmiah Biologi, 2026)
Body odor is a problem caused by the activity of microorganisms, one of which is the Pseudomonas aeruginosa bacteria by metabolizing sweat released by the body. The use of antiperspirant products is thought to reduce sweat production and bacterial decay . However, antiperspirants available in the market contain active chemicals that can cause irritation so it is necessary to use plant extracts as an alternative preparation of natural antiperspirant products. This study aims to determine the effectiveness of natural antiperspirant extracts of red shoot leaves (Syzygium myrtifolium Walp.) in inhibiting the growth of Pseudomonas aeruginosa bacteria that cause body odor. The method used is descriptive quantitative with parameters of simplicia and extract yield tests, extract characteristics, phytochemical screening, antibacterial effectiveness of extracts, physical quality tests of antiperspirants, antiperspirant effectiveness and Scanning Electron Microscope (SEM). The results of the study showed that the red shoot leaf extract meets the general standards of medicinal plant extracts and contains secondary metabolite compounds that are able to inhibit the growth of Pseudomonas aeruginosa bacteria with the formulated product producing suitable characteristics as an antiperspirant that is able to inhibit sweat production and the growth of Pseudomonas aeruginosa bacteria which is supported visually by Scanning Electron Microscope (SEM). Based on the results obtained, it is known that the natural antiperspirant red shoot leaf extract (Syzygium myrtifolium Walp.) has antibacterial effectiveness against Pseudomonas aeruginosa . Thus, the use of natural ingredients can be a solution to overcome the causes of body odor and reduce the use of conventional antiperspirant products that contain chemicals that are harmful to health.